2020
DOI: 10.1042/bcj20200560
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of TRPC6 and STIM2 in cytosolic and endoplasmic reticulum Ca2+ content in resting estrogen receptor-positive breast cancer cells

Abstract: TRPC6 forms non-selective cation channels activated by a variety of stimuli that are involved in a wide number of cellular functions. In estrogen receptor-positive (ER+) breast cancer cells, the store-operated Ca2+ entry has been reported to be dependent on STIM1, STIM2 and Orai3, with TRPC6 playing a key role in the activation of store-operated Ca2+ entry as well as in proliferation, migration and viability of breast cancer cells. We have used a combination of biotinylation, Ca2+ imaging as well as protein kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Altogether, these findings indicate that TRPC6 is involved in constitutive Ca 2+ entry in ppFurin-expressing MDA-MB-231 cells. Recent studies have reported constitutive activity of STIM2 in resting conditions [27,28]. Hence, we have investigated whether STIM2 expression is altered in ppFurin-expressing cells or upon TRPC6 expression silencing.…”
Section: Regulation Of Ca 2+ Mobilization By Ppfurinmentioning
confidence: 99%
“…Altogether, these findings indicate that TRPC6 is involved in constitutive Ca 2+ entry in ppFurin-expressing MDA-MB-231 cells. Recent studies have reported constitutive activity of STIM2 in resting conditions [27,28]. Hence, we have investigated whether STIM2 expression is altered in ppFurin-expressing cells or upon TRPC6 expression silencing.…”
Section: Regulation Of Ca 2+ Mobilization By Ppfurinmentioning
confidence: 99%
“…In contrast to Orai1, its homologue Orai3 is not sensitive to ROS, and the Orai1/Orai3 ratio determines if intracellular SOCE Ca 2+ signaling depend on ROS [65][66][67][68]. Both STIM2 and Orai3 subunits are dysregulated in different types of cancer and contribute to metastatic spread, proliferation, and reduced apoptosis [43,[67][68][69][70][71][72][73][74][75][76][77][78][79][80]. TRPM4 directly contributes to H 2 O 2 -dependent migration, possibly because H 2 O 2 prevents the desensi-tization of TRPM4 [59,81].…”
Section: General Mechanisms Of Trpm4mentioning
confidence: 99%
“…SOCE in MCF7, as well as in other ER+ breast cancer cell lines, exhibits significant phenotypic and functional differences compared to other cell types. For instance, while the expression of STIM1 in these cells is normal or low, STIM2 expression is slightly higher, and both Orai1 and Orai3 are overexpressed, especially Orai3 [9,10,28]. From the functional point of view, SOCE in MCF7 is mediated by STIM1, STIM2, and Orai3, in contrast to other breast cancer subtypes, such as TNBC cells, where SOCE is entirely dependent on STIM1 and Orai1 [9,10].…”
Section: Discussionmentioning
confidence: 91%